LIVELIHOOD RECOVERY AFTER LAND ACQUISITION FOR A NATIONAL STRATEGIC PROJECT: A CASE STUDY OF THE TUBAN OIL REFINERY, INDONESIA - Vida Andriani; Setiowati Setiowati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The construction of the Tuban Oil Refinery, which is included in the National Strategic Project (PSN), has a significant impact on the social, economic, and environmental aspects of the community around the project site, especially Wadung and Sumurgeneng Villages. This article aims to analyze the dynamics of people's lives after land acquisition and evaluate the effectiveness of the recovery program implemented by PT Pertamina. The research uses a qualitative-descriptive approach by collecting data through document studies, interviews, and field observations. The results of the study show that land acquisition has a positive impact on some land-owning farmers who receive considerable financial compensation, but it creates vulnerability for farm workers, smallholders, and ranchers who lose their source of livelihood and do not receive direct compensation. The recovery of people's lives is analyzed based on five types of assets: human, natural, social, physical, and financial. PT Pertamina responds to this impact through CSR programs such as relocation, job training, educational scholarships, and environmental and social programs for the surrounding community. While there has been an increase in physical and financial assets in some groups, long-term recovery requires sustained support and local community-based adaptive policies. This article recommends the need for integration between land acquisition, livelihood protection, and community capacity building in nation-scale development projects.